2013
DOI: 10.3389/fpsyg.2013.00383
|View full text |Cite
|
Sign up to set email alerts
|

Development of response inhibition in the context of relevant versus irrelevant emotions

Abstract: The present study examined the influence of relevant and irrelevant emotions on response inhibition from childhood to early adulthood. Ninety-four participants between 6 and 25 years of age performed two go/nogo tasks with emotional faces (neutral, happy, and fearful) as stimuli. In one go/nogo task emotion formed a relevant dimension of the task and in the other go/nogo task emotion was irrelevant and participants had to respond to the color of the faces instead. A special feature of the latter task, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 27 publications
4
31
2
Order By: Relevance
“…In contrast to studies that reported a linear development of hot inhibitory control abilities (Prencipe et al., ; Schel & Crone, ; Tottenham et al., ), we found that Hot Stroop interference effects were greater in adolescents than in children and adults; that is, they followed an inverse U‐shaped developmental pattern consistent with an adolescent‐specific model of inhibitory control development (Somerville et al., ). Thus, the present study advocates in favor of the neurodevelopmental model of Casey (e.g., Casey, ), which views adolescence as a time‐window characterized by an imbalance between an immature prefrontal network and a hyperactive subcortical network (Casey et al., ; Casey & Caudle, ; Casey, Jones, & Somerville, ), over Zelazo's model (Zelazo & Müller, ).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to studies that reported a linear development of hot inhibitory control abilities (Prencipe et al., ; Schel & Crone, ; Tottenham et al., ), we found that Hot Stroop interference effects were greater in adolescents than in children and adults; that is, they followed an inverse U‐shaped developmental pattern consistent with an adolescent‐specific model of inhibitory control development (Somerville et al., ). Thus, the present study advocates in favor of the neurodevelopmental model of Casey (e.g., Casey, ), which views adolescence as a time‐window characterized by an imbalance between an immature prefrontal network and a hyperactive subcortical network (Casey et al., ; Casey & Caudle, ; Casey, Jones, & Somerville, ), over Zelazo's model (Zelazo & Müller, ).…”
Section: Discussioncontrasting
confidence: 99%
“…irrelevant in participants aged 6-25, and found that only task-relevant emotion had a strong effect on inhibition (Schel & Crone, 2013).…”
Section: Another Task That Measures Inhibitory Control and Attentionamentioning
confidence: 93%
“…Both task demands and environmental stimuli, such as visual images, temperatures, sounds and smells, have an effect on the way children process incoming information (e.g., Bush, Alkon, Obradovic, Stamperdahl, & Boyce, 2011;McManis, Bradley, Berg, Cuthbert, & Lang, 2001;Sharp, van Goozen, & Goodyer, 2006;Schell & Crone, 2013;Tottenham, Hare, & Casey, 2011). Environmental stimuli including emotionally loaded stimuli, also referred to as affective stimuli, may capture and divert attention regardless of their relevance to ongoing tasks (Dolcos & McCarthy, 2006), affecting children's cognitive control processes (Tottenham et al, 2011;Schell & Crone, 2013) and eliciting a range of subjective and autonomic responses (McManis et al, 2001;Shapiro, Sgan Cohen, Parush, & Melmed, 2009;Sharp et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental stimuli including emotionally loaded stimuli, also referred to as affective stimuli, may capture and divert attention regardless of their relevance to ongoing tasks (Dolcos & McCarthy, 2006), affecting children's cognitive control processes (Tottenham et al, 2011;Schell & Crone, 2013) and eliciting a range of subjective and autonomic responses (McManis et al, 2001;Shapiro, Sgan Cohen, Parush, & Melmed, 2009;Sharp et al, 2006). Shapiro et al (2009), for example, demonstrated the significant value of a sensory adapted environment that included special lighting effects, relaxing music, vibrations, and aromas on the comfort level of children with and without developmental disabilities undergoing dental treatment as measured via electrodermal activity.…”
Section: Introductionmentioning
confidence: 99%